The effect of triiodothyronine on changes of membrane fluidity in regenerating rat liver - Drahota, Z; Rauchová, H; Sedlák, V; Koci, J; Cervinková, Z (Physiological research, 1999)
The increase of the membrane fluidity during the early phase of liver regeneration after partial hepatectomy was described in literature in plasma membrane and in microsomes. We found similar changes also in isolated mitochondria and in crude total membrane fraction of the liver homogenate. The administration of triiodothyronine to rats before partial hepatectomy diminished the increase of the membrane fluidity in the regenerating liver by 50%. Triiodothyronine effect is explained by hormonal modification of lipid metabolism in the regenerating liver.
Keywords: potkani Wistar; buněčná membrána; játra; fluidita membrány; Rats; Triiodothyronine; Animals; Cell Membrane; krysa rodu Rattus; Liver; mužské pohlaví; Liver Regeneration; Male; Rats, Wistar; zvířata; Membrane Fluidity; regenerace jater; trijodthyronin